Hospital-diagnosed atopic dermatitis and long-term risk of myocardial infarction: a population-based follow-up study. Issue 11 (11th November 2016) - Riis, Jette Lindorff; Vestergaard, Christian; Hjuler, Kasper Fjellhaugen; Iversen, Lars; Jakobsen, Lars; Deleuran, Mette S; Olsen, Morten
Abstract : Objective: Atopic dermatitis (AD) is an inflammatory skin disorder with a childhood prevalence reaching 20%. An estimated 50% of patients have a life-long chronic course. The purpose of this study was to estimate the risk of first-time myocardial infarction (MI) in patients with AD compared with a general population cohort. Design: Cohort study. Setting: Denmark. Participants: Using population-based medical registries, we identified individuals born in Denmark from 1947 to 1983 with at least two hospital-diagnoses of AD following inpatient admissions or hospital-based outpatient visits at any age from 1977 to 2013. Individuals with AD were matched with general population controls (10:1) for birth-year and gender. Unique personal identifiers permitted unambiguous data linkage. Primary outcome measures: Follow-up began on the date of AD diagnosis (index date for general population controls) and continued until death, emigration, MI or the year 2013. We computed the 15-year-cumulative incidence of MI following a diagnosis of AD. Comparing patients with AD with the general population cohort, we computed HRs of MI presented with 95% CIs and adjusted for history of diabetes mellitus, hypertension, hyperlipidaemia or stroke, educational level, birth-year and sex. Results: We identified 4814 patients diagnosed with AD. The cumulative incidence of MI was 0.6% for patients with AD and 0.4% for their matched controls. The corresponding adjusted HR was 1.74 (1.21 to 2.49). The HR for patients who were not in need of systemic treatment was 1.58 (1.02 to 2.45) and it was 2.40 (1.27 to 4.45) for those who were treated with azathioprine, methotrexate or cyclosporine. Conclusions: Hospital-diagnosed AD was associated with increased risk of MI compared with the general population.